CO2 carbonation of olivine-admixed marine clay: Suitability for bottom liner application - Emmanuel E.; Anggraini V.; Syamsir A.; Asadi A. (MDPI AG, 2023)
This paper focuses on employing an optimization approach in evaluating the hydraulic conductivity (HC) of CO2-carbonated olivine-admixed marine clay for possible utilization as a hydraulic barrier in engineered landfills to minimize leachate migration. The attainable region technique was used to optimize the olivine particle size during the grinding process before treating the soil, while the response surface methodology was used in designing the experiments, evaluating the results, and optimizing the variables responsible for reducing the HC of the CO2-carbonated olivinetreated clay. The effects of the control factors (olivine content, carbonation time, and carbonation pressure) on the response (HC) were studied by variance analysis. The factors and the response were related by a developed regression model. Predicted values from the model were in concurrence with their experimental counterparts. The results show that the HC of the CO2-carbonated olivine-treated clay samples met the Malaysian regulatory specification of ?10-8 m/s for liner utilization. The optimum conditions were 24.7% olivine content, 20.1 h carbonation time, and 161 kPa carbonation pressure, which decreased the HC by approximately 98%. CO2-carbonation and olivine blend proved to be a sustainable technique to reduce the clays HC for possible application as a liner material in engineered landfills. 2021 by the authors. Licensee MDPI, Basel, Switzerland.